NCIT Enabled OPNET Based Design of a Digital Substation for IEC 61850-9-2 Implementation - Kumar, S.; Islam, Syed; Das, Narottam; Gardner, B. (Institute of Electrical and Electronics Engineers, 2016)
IEEE Reliable protection and communication are the key features in a digital substation from protection, control and automation perspective. Implementation of digital protection in high voltage (HV) substations could provide increased reliability, optimized maintenance cost and improved communication capabilities. The application of IEC 61850-9-2 process bus technology in a utility substation has reduced the fault diagnosis downtime due to decreased number of nodes likely to be tested for investigation. Additionally, manufacturers are offering new smart primary plants that have intelligent features built within to makes it a fit case to replace Conventional Instrument Transformers (CITs). These Non-Conventional Instrument Transformers (NCITs) coupled with Merging Units and Intelligent Electronic Devices (IEDs) provide better accuracy, transient response and wider bandwidth when implemented in a process bus system guided by IEC 61850-9-2 standard. It is seen that use of NCIT could mitigate issues arising out of CIT failures, provide better safety, reliability, and increased asset life. At present, majority of the CITs operating in the air insulated and gas insulated high voltage (HV) substations are either oil filled or SF6 type which has few environmental issues in the event of a catastrophic failure or leakage. NCITs have better performance as compared to CITs. However, before these high voltage NCITs could find their way in a mass implementation in smart grids and digital substations, there is a need for modelling and simulation at the design stage for its application as per IEC61850-9-2 process bus and its successful implementation. Optimized Network Engineering Tool (OPNET) or Riverbed Modeler is a popular simulation software for such design and modeling of Ethernet networks. This paper presents a model of OPNET software for the simulation of a NCIT based on digital substation in a process bus environment.